PROFIL PELAKSANAAN ASESMEN SECARA DARING DALAM MENILAI PENGUASAAN KONSEP DAN EFIKASI DIRI SISWA SMA - Deasyca Yolanda; Aa Juhanda; Gina Nuranti (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2021)
The purpose of this study was to describe the implementation of online assessment in assessing the concept and self-efficacy of high school biology material. The research method used was descriptive qualitative research. The study population was high school students in Sukabumi Regency. The samples used were 76 students of class X and XI in Sukabumi Regency and 2 Biology teachers. Data collection instruments in the form of interviews and questionnaires. The results showed that the student's questionnaire had a percentage of 68.11 (fair enough category), meaning that the implementation of the assessment for mastering the concepts and self-efficacy of students was quite good. The results of teacher interviews stated that the Assessments carried out were not varied due to challenges in daring learning. The bloom taxonomy used by Biology teachers at SMAN 1 Jampang Tengah in measuring concept mastery was C1, C2, C3, and C4 and not used C5, and C6. In addition, the teacher assessed peer-to-peer that made students understand the material being taught and affect student self-efficacy. It appears that the implementation of online assessment at the Sukabumi Regency Senior High School is already in the good category. It might need innovation and improvement in the future to control students' concepts and self-efficacy.